(untitled) (Journal of Politica Governo, 2026)
States today face overlapping global crises, including financial instability, pandemics, climate change, migration, geopolitical conflict, and widening inequality. These crises no longer operate in isolation but interact in what scholars describe as a polycrisis. This article analyzes how state capacity determines the ability to manage such compounded socio-economic shocks. Using a systematic literature review covering 2006–2025 and comparative analysis across political regimes and regions, the study identifies key determinants of crisis governance. Findings indicate that state capacity is not merely coercive strength but a multidimensional construct encompassing institutional quality, democratic legitimacy, multilevel coordination, and integration within global governance frameworks. Democratic regimes tend to demonstrate stronger long-term resilience, although authoritarian systems may respond more rapidly in early crisis stages. Welfare states show adaptive variation under globalization pressures, while fragile states face compounded challenges from corruption, sanctions, and external conditionalities. Multilevel and hybrid governance arrangements emerge as critical mechanisms for navigating polycrisis conditions. However, political short-termism, bureaucratic decline due to sanctions, and fragmentation of international organizations constrain effective and equitable crisis management. The article concludes that anticipatory and cooperative governance, supported by robust domestic institutions and coordinated global frameworks, is essential for sustaining socio-economic stability under conditions of systemic global disruption.